The Synthesis of Methyl-2, 4, 6-Trideoxy--D-Glycero-3-Hexosulo Pyranoside and Methyl-3,4, 6-Trideoxy- -D-Glycero-2-Hexosulo Pyranoside - Othman, Adil A.; Szarek, Walter A. (European Journal of Applied Sciences, 2022)
Two trideoxy keto sugars namely methyl-2,4,6-trideoxy-µ-D-glycero-3-hexasulo pyranoside (7a) and methyl-3,4,6-trideoxy-µ-D-glycero-2-hexosulo pyranoside (10) have been prepared from-D-glucose. The synthesis of 7a was achieved by irradiation of methyl -4,6-dideoxy-2-O-tosyl-µ-D-erythro hexosulo pyranoside (6a). The another ketone 10 was prepared by an oxidation of methyl-3,4,6-trideoxy-µ-D-erythro and threo hexapyranosides (9a and 9b). Intermediates and final products were characterized by IR, 1H-NMR spectroscopy and elemental analysis.